2004
DOI: 10.1074/jbc.m308710200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Src-induced Dynamin-2 Phosphorylation in Caveolae-mediated Endocytosis in Endothelial Cells

Abstract: Albumin transcytosis, a determinant of transendothelial permeability, is mediated by the release of caveolae from the plasma membrane. We addressed the role of Src phosphorylation of the GTPase dynamin-2 in the mechanism of caveolae release and albumin transport. Studies were made in microvascular endothelial cells in which the uptake of cholera toxin subunit B, a marker of caveolae, and 125 I-albumin was used to assess caveolaemediated endocytosis. Albumin binding to the 60-kDa cell surface albumin-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
192
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(199 citation statements)
references
References 41 publications
7
192
0
Order By: Relevance
“…In the present study, we observed an increase of caveolin-1 expression in MP-treated cells, which was associated with a decrease of eNOS activity. Caveolin-1 is phosphorylated on Tyr 14 by Src family kinases (36 -38), which leads to caveolae fission (39). Here, we reported that MPs increased caveolin-1 expression and decreased its phosphorylation on Tyr 14 by a mechanism insensitive to PI3K and MAPK inhibitors, while the NO production is decreased as reported above.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, we observed an increase of caveolin-1 expression in MP-treated cells, which was associated with a decrease of eNOS activity. Caveolin-1 is phosphorylated on Tyr 14 by Src family kinases (36 -38), which leads to caveolae fission (39). Here, we reported that MPs increased caveolin-1 expression and decreased its phosphorylation on Tyr 14 by a mechanism insensitive to PI3K and MAPK inhibitors, while the NO production is decreased as reported above.…”
Section: Discussionsupporting
confidence: 64%
“…While tyrosine phosphorylation has been observed in response to various ligands (13)(14)(15)(25)(26)(27)(28), this event is thought to play a role in the regulation of ligand-induced uptake of various receptors. However, the mechanisms involved in regulating Dyn2 function during secretion and, more specifically, whether Src kinase-mediated phosphorylation plays a role in this process have remained largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there appears to be a selective dynamin dependence for apical vs. basolateral membrane targeted cargo in polarized cell models, where other proteins including CtBP1/BARS have been reported to play a role (10)(11)(12). Moreover, Dyn2 is a substrate of Src and has been shown to be phosphorylated by this kinase during the activation and subsequent endocytic internalization of specific membrane receptors (13)(14)(15). In this study, we provide evidence that Src kinase, through regulation of Dyn2, acts to control Golgi dynamics in both normal and neoplastic cells as well as vesiculation of the TGN during the secretory process.…”
mentioning
confidence: 99%
“…Because Dyn2 is phosphorylated by an active Src kinase (pSrc) to achieve its biologically active form (pDyn2),16, 34 we quantified the total and phosphorylated forms of Src and Dyn2 in liver homogenates. As shown in Figure 1A, chronic EtOH administration did not affect the total content of either protein (bottom band in each panel).…”
Section: Resultsmentioning
confidence: 99%
“…Once phosphorylated, Dyn2 catalyzes constriction and scission of endocytic vesicles at the plasma membrane, thereby releasing early endosomes to the cell interior 11, 12, 13. The Src‐kinase is a nonreceptor protein tyrosine kinase that is activated during stress conditions and regulates cytoskeletal‐dependent membrane trafficking by phosphorylation of specific substrates, including Dyn2 14, 15, 16, 17. Inhibition of Dyn2 by small molecule inhibitors impairs lipophagy‐dependent LD breakdown in hepatic cells.…”
mentioning
confidence: 99%